2015
DOI: 10.1371/journal.pone.0129803
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modification Agents Improve Gene-Specific Methylation Reprogramming in Porcine Cloned Embryos

Abstract: Incomplete DNA methylation reprogramming in cloned embryos leads to poor cloning efficiency. Epigenetic modification agents can improve genomic methylation reprogramming and the development of cloned embryos, however, the effect of epigenetic modification agents on gene-specific methylation reprogramming remains poorly studied. Here, we investigated DNA methylation reprogramming of pluripotency (Oct4) and tissue specific (Thy1) genes during early embryo development in pigs. In this study, we found that compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 32 publications
0
33
0
Order By: Relevance
“…The epigenetic modification agent 5-aza-dC or TSA improved the expression patterns of pluripotent transcription factors ( Oct4 , Nanog ) resulting in high development of cloned embryos [3234]. In this study, the pluripotent markers Oct4 and Nanog were examined and shown to have higher expression levels in the miR-148a-NT group relative to the miR-con-NT or con-NT groups.…”
Section: Discussionmentioning
confidence: 99%
“…The epigenetic modification agent 5-aza-dC or TSA improved the expression patterns of pluripotent transcription factors ( Oct4 , Nanog ) resulting in high development of cloned embryos [3234]. In this study, the pluripotent markers Oct4 and Nanog were examined and shown to have higher expression levels in the miR-148a-NT group relative to the miR-con-NT or con-NT groups.…”
Section: Discussionmentioning
confidence: 99%
“…OCT4 is required for the specification of inner cell mass lineage in mouse [36] as well as blastocyst formation in pig [37]. Furthermore, DNA and H3K9 demethylation could enhance the reprogramming efficiency and pluripotency through inducing the increased expression of OCT4 [21,38]. In mouse preimplantation embryos Cdx2 is essential for the specification of TE lineage and blastocyst formation and expansion [39].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of the artificial modifiers of epigenomically conditioned gene expression, gives rise to the inhibition of both chromatin condensation and transcriptional repression of the genomic DNA of cultured somatic cells that provide a source of donor nuclei for the reconstruction of enucleated oocytes and subsequent generation of cloned embryos (Saini et al, ; Su et al, ; Wang, Zhang, et al, ; Wang, Su, et al, ). On the one hand, those epigenetic modifiers represent not only the subclass of highly specific extrinsic HMT inhibitors (HMTi) such as G9A (H3K9) HMTi, whose pivotal member is diazepin‐quinazolin‐amine derivative termed BIX‐01294 (Cao et al, ; Huang et al, ), but also the subclass of ectopic non‐specific DNMT inhibitors, whose most important members are: (a) 5‐aza‐2′‐deoxycytidine (5‐aza‐dC) (Huan, Wang, et al, ; Huan, Wu, et al, ; Huan et al, , ; Ning et al, ); and (b) zebularine (a nucleoside analog of cytidine; Diao et al, ). On the other hand, they represent the subclass of ectopic non‐selective HDAC inhibitors (HDACi), whose main members are (a) TSA (Huan, Wang, et al, ; Huan, Wu, et al, ; Huan et al, ; Opiela et al, ; Samiec et al, ); (b) scriptaid (SCPT) (Liang, Zhao, Choi, Kim, & Cui, ; Xu et al, ; Zhang et al, ); (c) oxamflatin (Hou et al, ; Mao et al, ); (d) sodium butyrate (NaBu) (Kumar et al, ; Liu et al, ); (e) m ‐carboxycinnamic acid bis hydroxamide (CBHA) (Song et al, ); (f) panobinostat, also known as LBH589 (Jin et al, ); (g) abexinostat, also termed PCI‐24781 (Jin et al, ); (h) quisinostat, also called JNJ‐26481585 (Jin, Guo, et al, ); and (i) dacinostat, also named as LAQ824 (Jin, Lee, Taweechaipaisankul, Kim, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, those epigenetic modifiers represent not only the subclass of highly specific extrinsic HMT inhibitors (HMTi) such as G9A (H3K9) HMTi, whose pivotal member is diazepin‐quinazolin‐amine derivative termed BIX‐01294 (Cao et al, ; Huang et al, ), but also the subclass of ectopic non‐specific DNMT inhibitors, whose most important members are: (a) 5‐aza‐2′‐deoxycytidine (5‐aza‐dC) (Huan, Wang, et al, ; Huan, Wu, et al, ; Huan et al, , ; Ning et al, ); and (b) zebularine (a nucleoside analog of cytidine; Diao et al, ). On the other hand, they represent the subclass of ectopic non‐selective HDAC inhibitors (HDACi), whose main members are (a) TSA (Huan, Wang, et al, ; Huan, Wu, et al, ; Huan et al, ; Opiela et al, ; Samiec et al, ); (b) scriptaid (SCPT) (Liang, Zhao, Choi, Kim, & Cui, ; Xu et al, ; Zhang et al, ); (c) oxamflatin (Hou et al, ; Mao et al, ); (d) sodium butyrate (NaBu) (Kumar et al, ; Liu et al, ); (e) m ‐carboxycinnamic acid bis hydroxamide (CBHA) (Song et al, ); (f) panobinostat, also known as LBH589 (Jin et al, ); (g) abexinostat, also termed PCI‐24781 (Jin et al, ); (h) quisinostat, also called JNJ‐26481585 (Jin, Guo, et al, ); and (i) dacinostat, also named as LAQ824 (Jin, Lee, Taweechaipaisankul, Kim, & Lee, ). The initiation of chromatin decondensation and gene transcriptional activity is triggered both via highly specific and transient inactivation of G9A (H3K9) HMTs by BIX‐01294 (Cao et al, ; Huang et al, ) and via non‐specifically blocking the biocatalytic activity of either DNMTs by 5‐aza‐dC and zebularine (Diao et al, ; Saini et al, ) or HDACs by TSA, SCPT, oxamflatin, NaBu, CBHA, panobinostat, abexinostat, quisinostat and dacinostat (Jin, Lee, et al, ; Jin et al, , ; Jin, Guo, et al, ; Kumar et al, ; Song et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%